Accounting Procedures of Small Business Enterprises in Trans Nzoia County, Kenya. - Chesoli, Dr. Joshua W. (IJRDO - Journal of Business Management, 2017)
Small enterprises all over the world are the bedrock of economic development, as they are the basis for growth of developing economies. The present effort is therefore to look into the accounting procedures of selected small and medium scale enterprises in Trans Nzoia County, Kenya. Structured questionnaire were randomly distributed to sampled businesses. The data collected were presented in tabular form and analyzed using simple percentages, frequency counts and least square linear regression model to test set hypothesis, which was run on statistical package for social sciences (SPSS). The findings showed that proper accounting records has great influence on the effective operation of sole proprietor and that capital investment also has effects on the potential growth of one man businesses. This study recommended that good accounting practices will improve the effective operations of small and medium scale enterprises and even sole proprietors